Factors associated with non-enrollment in national health insurance scheme: perspectives from multiple stakeholders scheme in Kaski district. - Adhikari, Anju (2020)
ABSTRACT: Background: National health insurance is a social security program which is run to achieve equitable health outcome by ensuring universal health coverage. This is family based program to enable its citizens to access quality health care services without placing financial burden on them. Objective was to assess the factors associated with non-enrollment in national health insurance scheme from the perspectives of multiple stakeholders. Methods: This study was based on the cross-sectional design among 492 households (246 non-enrolled and 246 enrolled) of Kaski district, Nepal from May to August 2020. Data were gathered by mixed method Face to face interview was done to collect quantitative data whereas for qualitative KII of multiple stakeholders were recorded. Quantitative data were entered in EpiData and analyzed by SPSS. Multiple logistic regressions were performed to describe sample characteristics and identify factors associated with non-enrollment. Regarding qualitative data first audio taped interviews were transcribed and manually content analysis was done. Results: Major (26.0%) reasons of non-enrollment in the NHIS were household members are mostly healthy and no need to be enrolled followed by (22.0%) not interested in the scheme. Of the non-enrolled households nearly half (45.1%) were not willing to join the NHIS in the future. Households having no elderly population in the family were 2.06 times less likely to enroll in the scheme (AOR=2.060, CI=1.1413.721, p<0.01). Similarly the odds of non-enrollment increases with the decreasing wealth quintile of the family. Family who perceived their family health status good were less likely to join the scheme. Households who had poor or average knowledge on the scheme were almost 5 times more likely to non-enrollment (AOR=4.641, CI=2.841-7.582, p<0.001). In addition that individual along with system wide factors contributes to non-enrollment. Conclusion: Factors that determine the non-enrollment are having no elderly population in the home, poor wealth quintile, self-perceived health status and knowledge on NHIS, individual as well as system factors. Present nature of adverse selection of the scheme pressures about the sustainability of the program. Key words: NHIS, Non-enrollment, Factors, Multiple stakeholders, Nepal